Changes of arterial pressure following relief of obstruction in adults with hydronephrosis. (2nd October 2018) - Al-Mashhadi, Ammar; Häggman, Michael; Läckgren, Göran; Ladjevardi, Sam; Nevéus, Tryggve; Stenberg, Arne; Persson, A. Erik G.; Carlström, Mattias
Abstract: Background: As much as 20% of all cases of hypertension are associated with kidney malfunctions. We have previously demonstrated in animals and in pediatric patients that hydronephrosis causes hypertension, which was attenuated by surgical relief of the ureteropelvic junction (UPJ) obstruction. This retrospective cohort study aimed to investigate: (1) the proposed link between hydronephrosis, due to UPJ obstruction, and elevated arterial pressure in adults; and (2) if elevated blood pressure in patients with hydronephrosis might be another indication for surgery. Materials and methods: Medical records of 212 patients undergoing surgical management of hydronephrosis, due to UPJ obstruction, between 2000 and 2016 were assessed. After excluding patients with confounding conditions and treatments, paired arterial pressures (i.e. before/after surgery) were compared in 49 patients (35 years old; 95% CI 29–39). Split renal function was evaluated by using mercaptoacetyltriglycine (MAG3) renography before surgical management of the hydronephrotic kidney. Results: Systolic (−11 mmHg; 95% CI 6–15 mmHg), diastolic (−8 mmHg; 95% CI 4–11 mmHg), and mean arterial (-9 mmHg; 95% CI 6–12) pressures were significantly reduced after relief of the obstruction ( p < 0.001). Split renal function of the hydronephrotic kidney was 39% (95% CI 37–41). No correlations were found between MAG3 and blood pressure level before surgery or between MAG3 and the reduction of blood pressure after surgical management of the UPJ obstruction. Conclusions: In adults with hydronephrosis, blood pressure was reduced following relief of the obstruction. Our findings suggest that elevated arterial pressure should be taken into account as an indication to surgically correct hydronephrosis.